2021
DOI: 10.1097/jsm.0000000000000939
|View full text |Cite
|
Sign up to set email alerts
|

Medical Encounters in a 90-km Ultramarathon Running Event: A 6-year Study in 103 131 Race Starters—SAFER XVII

Abstract: Objective: To determine the incidence and nature of illness-related medical encounters (MEs) at a 90-km, ultramarathon, mass, community-based, endurance running event. Design: Retrospective, descriptive epidemiological study. Setting: Comrades Marathon (90 km), South Africa. Participants: One lakh three thousand one hundred thirty-one race starters over 6 years (2014)(2015)(2016)(2017)(2018)(2019). Independent Variables: Incidence of moderate and serious/life-threatening MEs. Main Outcome Measures: All MEs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…18 In a recent study on the Comrades Marathon, a 90-km road race in South Africa, the overall incidence MEs was 19.1 per 1000 starters, and the incidence of serious/life-threatening MEs was reported at 1.8 per 1000 starters (9% of all MEs). 22 Although in the Dam tot Damloop the overall incidence of MEs was lower (2.8 per 1000 starters), the proportion of serious/life-threatening MEs in the Dam tot Damloop was higher (44% of all MEs). This illustrates how high a proportion of MEs are serious/life-threatening in the Dam tot Damloop compared with other races.…”
Section: Discussionmentioning
confidence: 92%
“…18 In a recent study on the Comrades Marathon, a 90-km road race in South Africa, the overall incidence MEs was 19.1 per 1000 starters, and the incidence of serious/life-threatening MEs was reported at 1.8 per 1000 starters (9% of all MEs). 22 Although in the Dam tot Damloop the overall incidence of MEs was lower (2.8 per 1000 starters), the proportion of serious/life-threatening MEs in the Dam tot Damloop was higher (44% of all MEs). This illustrates how high a proportion of MEs are serious/life-threatening in the Dam tot Damloop compared with other races.…”
Section: Discussionmentioning
confidence: 92%
“…Entrants with these underlying risk factors and chronic medical conditions are at higher risk of a ME on race day. CVD risk factors, history of CVD, respiratory disease and medication use are the most important risk factors and medical conditions in screening tools 15,16,20 . The most significant under‐reporting was in the CVD risk factors category (10.3% lower using the ABBR tool) followed by prescription medication use (6.5% less) and respiratory disease (5.7% less).…”
Section: Discussionmentioning
confidence: 99%
“…The race is run between the cities of Durban and Pietermaritzburg (in Kwa‐Zulu Natal province of South Africa), alternating directions each year. We recently reported that the incidence of MEs during this event is one of the highest, compared with other marathon and ultra‐marathon races, with 1 in 556 race starters developing a serious/life‐threatening ME 16 …”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations